Tuning the strength and ductility balance of a TRIP titanium alloy. (15th March 2021) - Ellyson, Benjamin; Klemm-Toole, Jonah; Clarke, Kester; Field, Robert; Kaufman, Michael; Clarke, Amy
Abstract: Titanium (Ti) alloys are ubiquitous in the aerospace, defense, and biomedical industries for their high strength to density ratios and good corrosion resistance. Ti alloys are typically optimized for strength, but improved work hardening characteristics and ductility would broaden their use in engineering applications. Here we show desirable combinations of strength and ductility in Ti-10V-2Fe-3Al (wt.%), including a fourfold increase in yield strength without commensurate losses in ductility, overcoming the classic strength/ductility tradeoff. This is achieved by nanoscale ω phase precipitates produced by natural and artificial aging, in concert with TRansformation Induced Plasticity (TRIP). Opportunity exists to tailor these strengthening mechanisms to design microstructural and mechanical response, opening up the performance landscape for lightweight Ti alloys for structural applications, analogous to the design of advanced high strength steels that result in lightweighting and improved crashworthiness for transportation applications. Graphical abstract: Image, graphical abstract